Effectiveness of Citronella Extract (Cymbopogon nardus) Mouthwash From Microwave-Assisted Extraction Method Against Streptococcus mutans - Komala, Oom; Mahyuni, Siti; Pradiningsih, Anna; Dewi, Elfrieda Kusuma (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2024)
Cymbopogon nardus, or citronella has a distinctive aroma is known as a source of essential oils. Extract of citronella can be use as mouthwash to reduce bad breath and protect teeth from bacteria that cause dental caries. C. nardus contains antibacterial compounds such as flavonoid, essential oils, polyphenols, and saponin which are also act as antioxidant compounds. This research was carried out to formulate mouthwash using citronella extract and determine the antibacterial activity of the citronella mouthwash against S. mutans bacteria using disc diffusion method. The microwave  extraction method (MAE) was used to obtain extract using  70 % and  96 % ethanol as  a solvents. The mouthwash were made in 3 formulas i.e.  formula 1, formula 2, and formula 3 each contain 25 % w/v, 30 % w/v, and 35 % w/v) respectively. The quality of mouthwash includes organoleptic, pH, viscosity and hedonic was evaluated and antibacterial activity was determined by measuring the value of minimum inhibitory concentration (MIC) and diameter of inhibition zone. The MIC value of citronella extract was achieved at concentration 20 %. All mouthwash formula met the requirements for a good mouthwash. Formula 1 was the most preferred formula by the panelists based on the hedonic test.  Formula 3 had the strongest antibacterial activity with diameter inhibitory of 17.6 ± 0.52 mm. It was concluded that citronella mothwash has the potential to be developed into an antibacterial mouthwash.